Nature-Based Learning in Improving Student Learning Achievement: A Systematic Literature Review - Darni Yulianti; Chairani Chairani; Muhammad Fahreza W (CV. Rayyan Dwi Bharata, 2023)
This study aims to conduct a literature study on nature-based learning for English subjects. The research method used is Systematic Literature Review (SLR). In this study data collection was carried out by reviewing books, articles and journals. Based on this research it was found that nature-based learning can make students free to explore and interact directly with the environment. This makes students not only accept but become actors in the learning process. The results of the study also show that the use of nature- and environment-based learning models has proven effective in increasing English vocabularies and improving language skills, namely listening, reading, writing, and speaking. The results of the study show that the use of nature and environment-based learning is proven to be able to improve the results of mastery of English vocabulary well and is proven by the increase in the results of students' learning achievement.